Robustness evaluation of three friction compensation methods for point-to-point (PTP) positioning systems - Wahyudi, Martono; Sato, Kaiji; Shimokohbe, Akira (Elsevier, 2005)
Friction is one of the major contributing factors for problems associated with accuracy in positioning systems. The problem becomes more complicated because of variation of the friction. Due to this fact, the objective of this paper is to compare experimentally two control methods for point-to-point (PTP) positioning system in the presence of friction and its variation. The first controller is nominal characteristic trajectory following (NCTF) controller. The second controller is PD controller with smooth robust nonlinear feedback (SRNF) compensator. Two controllers are compared in terms of not only effectiveness of the controller to compensate the friction, but also robustness to inertia and friction variations. The results demonstrate that the NCTF controller is much more robust to inertia and friction variations than PID controller with SRNF compensator.